Gap between Expectations and Experiences of Equity in Public Schools: A Pupils’ Perspective - Muhammad Uzair-ul-Hassan (PJE, 2023)
The study investigated into the lens of pupils from public sector that what constitutes fair and equitable schools in Pakistan. Also the study explored pupils’ expectations from school, how the schools can be transformed into equitable schools in which all students are treated equally and fairly. The study used quantitative approach with multistage sampling in two districts of Punjab, Pakistan. Questionnaire had been conducted on 434 pupils aged between 14-15 years of 9th and 10th class. The return rate of the questionnaire was 85%. Results of descriptive statistical analysis show that pupils receive equitable as well as inequitable treatment with respect to punishment, rewards and marks awarded by teachers in public schools. Results further show that wider the inequitable experiences of pupils in schools, greater are the equity expectations from schools. Also the pupils with various backgrounds differ significantly from each other in terms of inequitable experiences in schools. It is concluded that equitable public school would be the one in which all students are treated in an equitable manner irrespective of differences.